2016
DOI: 10.1021/acscatal.6b01656
|View full text |Cite
|
Sign up to set email alerts
|

SO2 Poisoning of the NH3-SCR Reaction over Cu-SAPO-34: Effect of Ammonium Sulfate versus Other S-Containing Species

Abstract: SO2 poisoning of NH3-SCR over Cu-SAPO-34 was studied, specifically to evaluate the forms/states of stored S and the effect of such species on low-temperature NO x reduction activity. Two primary sulfur species types were observed and were found to be interchangeable depending on whether NH3 was available or not. In one case both ammonium sulfate and Cu sulfate species could be present and in the other only Cu sulfate species. Cu sulfate, in the absence of ammonia, was found in three different states/forms, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 27 publications
7
86
0
Order By: Relevance
“…The impact of SO2 at temperatures above 350 °C is clearly less, indicating that deactivation by SO2 is mainly relevant for the low-temperature performance, in agreement with earlier observations. [13][14][15][16][17][18][19][20][21][22][23][24] The low-temperature activity after SO2 exposure is partially restored by heating the Cu-CHA catalysts to 550 C in SO2-free gas ( Figure 1B). 13,14,17 The changes in the deactivation of NH3-SCR activity with time of SO2 exposure are illustrated in Figure 2A, which shows the deactivation, according to Eq.…”
Section: Nh3-scr Activity and Impact Of So2 Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The impact of SO2 at temperatures above 350 °C is clearly less, indicating that deactivation by SO2 is mainly relevant for the low-temperature performance, in agreement with earlier observations. [13][14][15][16][17][18][19][20][21][22][23][24] The low-temperature activity after SO2 exposure is partially restored by heating the Cu-CHA catalysts to 550 C in SO2-free gas ( Figure 1B). 13,14,17 The changes in the deactivation of NH3-SCR activity with time of SO2 exposure are illustrated in Figure 2A, which shows the deactivation, according to Eq.…”
Section: Nh3-scr Activity and Impact Of So2 Exposurementioning
confidence: 99%
“…Ultra-low sulfur diesel contains less than 10 wt ppm (Europe) or 15 wt ppm (US) sulfur, and the SO2 concentration in the exhaust gas typically reaches a few ppmv, which is nevertheless sufficient to reduce the low-temperature activity of the Cu-CHA catalysts significantly. [13][14][15][16][17][18][19][20][21][22][23][24] To be able to preserve the good lowtemperature activity, it is important to understand the impact of SO2 on the NH3-SCR activity of Cu-CHA based catalysts. We have recently shown that deactivation of Cu-CHA catalysts depends on the total SO2 exposure, which is the product of the SO2 concentration and the exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the effect of NO and NH3 on SO2-poisoning is the formation of ammonium sulfate, which may infer mass transfer limitations by pore-blocking [14][15][16]. However, ammonium sulfate decomposes at about 350 °C, and can therefore feasibly be removed [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the effect of NO and NH3 on SO2-poisoning is the formation of ammonium sulfate, which may infer mass transfer limitations by pore-blocking [14][15][16]. However, ammonium sulfate decomposes at about 350 °C, and can therefore feasibly be removed [16]. Moreover, the presence of NO and NH3, or release of NH3 from ammonium sulfate, has a suggested beneficial effect on the regeneration of SO2-poisoned catalysts, due to the reducing properties of the SCR gas mixture and NH3 [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…Wijayanti et al [23] studied the SO 2 poisoning effects and found that the main reason for the deactivation is the formation of copper sulfates, resulting in the loss of redox properties. Jangjou et al [24] reported the S species formed on Cu 2+ at 6MR by DRIFT study. On the basis of such observations, the formation of ammonium sulfates in a complex with Cu is claimed as the main mechanism for the loss of low-temperature deNO x activity.…”
Section: Introductionmentioning
confidence: 99%